Employment and Economic Performance: Jobs, Inflation and Growth. - Michie, J (Oxford University Press, 1997)
With the end of the post-war boom in the early 1970s, the world economy has experienced large scale unemployment. From an assumption that the unemployment problem had been solved, and that full employment could be maintained through demand management techniques, we now live in an entirely different world. Any suggestion of a return to full employment is met with questions of whether such a thing is possible, whether it would not lead to inflation or to excessive trade union power, or in the case of individual economies to unsustainable balance of payment deficits. The contributors to this volume ask whether full employment policies would be affordable. Would they lead to yawning fiscal deficits which would in the end require a U-turn in policy with unemployment reappearing? This contribution to current policy debate faces up to these questions and considers what would be involved in a move to much lower levels of unemployment.